Efficacy of Inpatient Rehabilitation After Left Ventricular Assist Device Implantation. Issue 1 (4th June 2016) - Yost, Gardner; Coyle, Laura; Milkevitch, Kristen; Adair, Roy; Tatooles, Antone; Bhat, Geetha
Abstract: Background: Left ventricular assist devices (LVADs) have become an increasingly popular and effective means for treating advanced heart failure. LVAD implantation requires extensive surgery and postoperative rehabilitation. The Functional Independence Measure (FIM) has been used to quantify functional gains in numerous patient populations, including those with stroke and spinal cord injury. This study investigated functional improvements in patients undergoing LVAD implantation using the FIM score. Objective: To assess functional improvements in patients with advanced heart failure who underwent LVAD implantation. Design: Retrospective. Setting: Inpatient rehabilitation unit. Subjects: Ninety consecutive patients who received acute inpatient rehabilitation after continuous flow LVAD implantation. Methods: Demographic, laboratory, and functional outcomes data including inpatient rehabilitation unit (IRU) length of stay (LOS), discharge disposition, and FIM score were collected for all patients. Paired t ‐tests were used to assess change in functional measures and laboratory data. Main Outcome Measures: Primary outcome measures included FIM gain, FIM efficiency, discharge disposition, rates of readmission after discharge from rehabilitation, and LOS in the rehabilitation unit. Results: The FIM gain was statistically significant at 28.4 ± 12.3 ( P < .001) and compared favorably with benchmarks for mean FIM gains at our facility (26.4), regionally (21.5), and nationally (22.7) for patients admitted to IRUs with a cardiac diagnosis. FIM efficiency (FIM gain/IRU LOS) was 1.9 ± 1.0 compared with the mean FIM efficiency at our facility (2.2), regionally (2.1), and nationally (2.2). Seventy‐four percent (n = 67) of patients were discharged directly home after inpatient rehabilitation, 17% (n = 16) were readmitted to the acute hospital service, and 8% (n = 7) required additional rehabilitation at a subacute rehabilitation facility. The IRU LOS was 16.2 ± 6.9 days. Conclusions: Our study indicates that most patients with an LVAD achieve clinically meaningful functional gains from acute inpatient rehabilitation, with the majority of patients being discharged home. Further studies need to be performed to analyze clinical outcomes after acute inpatient rehabilitation. Level of Evidence: IV